Teaching Dynamics, Public Speaking Anxiety, and Language Proficiency of Student Interns - Lava, Sharmaine L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This mixed-method research aimed to evaluate the teaching dynamics, public speaking anxiety, and language proficiency of student interns in Capiz during the Academic Year 2023-2024. A sample of 300 student interns, drawn from a total population of 1,137 across various teacher education programs, participated in the study. Additionally, nine teacher mentors, an internship supervisor, and nine student interns from Higher Education Institutions in Capiz were involved in the quali-tative component. Data collection employed a researcher-constructed questionnaire and focus group discussion guide, addressing variables such as teaching dynamics, public speaking anxiety, and language pro-ficiency. Statistical tools used included mean, standard deviation, ANOVA, and Pearson correlation coefficient, with an alpha level set at .05. The findings revealed that student interns demonstrated a "very high" level of teaching dynamics, excelling in classroom authority, communication, interaction, and expertise while showing a "high" lev-el of assessment knowledge. Significantly, public speaking anxiety was “moderate” across behavioral and emotional components. The interns exhibited "very high" language proficiency, particularly in writing, with "high" vocabulary, grammar, and reading comprehension levels. There were no significant differences in public speaking anxiety across teaching dynamics or language proficiency levels. However, a signifi-cant relationship was found between teaching dynamics and both pub-lic speaking anxiety and language proficiency. No significant relation-ship was found between language proficiency and public speaking anx-iety. These findings suggest that while student interns' teaching dy-namics and language proficiency are strong, addressing public speak-ing anxiety remains essential to further enhance their overall teaching effectiveness.